123456789101112131415161718192021222324252627282930313233343536373839404142434445464748495051525354555657585960616263646566676869707172737475767778798081828384858687888990919293949596979899100101102103104105106107108109110111112113114115116117118119120121122123124125126127128129130131132133134135136137138139140141142143144145146147148149150151152153154155156157158159160161162163164165166167168169170171172173174175176177178179180181182183184185186187188189190191192193194195196197198199200201202203204205206207208209210211212213214215216217218219220221222223224225226227228229230231232233234235236237238239240241242243244245246247248249250251252253254255256257258259260261262263264265266267268269270271272273274275276277278279280281282283284285286287288289290291292293294295296297298299300301302303304305306307308309310311312 |
- from sympy.core.containers import Tuple
- from sympy.core.function import Function
- from sympy.core.numbers import oo, Rational
- from sympy.core.singleton import S
- from sympy.core.symbol import symbols, Symbol
- from sympy.functions.combinatorial.numbers import tribonacci, fibonacci
- from sympy.functions.elementary.exponential import exp
- from sympy.functions.elementary.miscellaneous import sqrt
- from sympy.functions.elementary.trigonometric import cos, sin
- from sympy.series import EmptySequence
- from sympy.series.sequences import (SeqMul, SeqAdd, SeqPer, SeqFormula,
- sequence)
- from sympy.sets.sets import Interval
- from sympy.tensor.indexed import Indexed, Idx
- from sympy.series.sequences import SeqExpr, SeqExprOp, RecursiveSeq
- from sympy.testing.pytest import raises, slow
- x, y, z = symbols('x y z')
- n, m = symbols('n m')
- def test_EmptySequence():
- assert S.EmptySequence is EmptySequence
- assert S.EmptySequence.interval is S.EmptySet
- assert S.EmptySequence.length is S.Zero
- assert list(S.EmptySequence) == []
- def test_SeqExpr():
- #SeqExpr is a baseclass and does not take care of
- #ensuring all arguments are Basics hence the use of
- #Tuple(...) here.
- s = SeqExpr(Tuple(1, n, y), Tuple(x, 0, 10))
- assert isinstance(s, SeqExpr)
- assert s.gen == (1, n, y)
- assert s.interval == Interval(0, 10)
- assert s.start == 0
- assert s.stop == 10
- assert s.length == 11
- assert s.variables == (x,)
- assert SeqExpr(Tuple(1, 2, 3), Tuple(x, 0, oo)).length is oo
- def test_SeqPer():
- s = SeqPer((1, n, 3), (x, 0, 5))
- assert isinstance(s, SeqPer)
- assert s.periodical == Tuple(1, n, 3)
- assert s.period == 3
- assert s.coeff(3) == 1
- assert s.free_symbols == {n}
- assert list(s) == [1, n, 3, 1, n, 3]
- assert s[:] == [1, n, 3, 1, n, 3]
- assert SeqPer((1, n, 3), (x, -oo, 0))[0:6] == [1, n, 3, 1, n, 3]
- raises(ValueError, lambda: SeqPer((1, 2, 3), (0, 1, 2)))
- raises(ValueError, lambda: SeqPer((1, 2, 3), (x, -oo, oo)))
- raises(ValueError, lambda: SeqPer(n**2, (0, oo)))
- assert SeqPer((n, n**2, n**3), (m, 0, oo))[:6] == \
- [n, n**2, n**3, n, n**2, n**3]
- assert SeqPer((n, n**2, n**3), (n, 0, oo))[:6] == [0, 1, 8, 3, 16, 125]
- assert SeqPer((n, m), (n, 0, oo))[:6] == [0, m, 2, m, 4, m]
- def test_SeqFormula():
- s = SeqFormula(n**2, (n, 0, 5))
- assert isinstance(s, SeqFormula)
- assert s.formula == n**2
- assert s.coeff(3) == 9
- assert list(s) == [i**2 for i in range(6)]
- assert s[:] == [i**2 for i in range(6)]
- assert SeqFormula(n**2, (n, -oo, 0))[0:6] == [i**2 for i in range(6)]
- assert SeqFormula(n**2, (0, oo)) == SeqFormula(n**2, (n, 0, oo))
- assert SeqFormula(n**2, (0, m)).subs(m, x) == SeqFormula(n**2, (0, x))
- assert SeqFormula(m*n**2, (n, 0, oo)).subs(m, x) == \
- SeqFormula(x*n**2, (n, 0, oo))
- raises(ValueError, lambda: SeqFormula(n**2, (0, 1, 2)))
- raises(ValueError, lambda: SeqFormula(n**2, (n, -oo, oo)))
- raises(ValueError, lambda: SeqFormula(m*n**2, (0, oo)))
- seq = SeqFormula(x*(y**2 + z), (z, 1, 100))
- assert seq.expand() == SeqFormula(x*y**2 + x*z, (z, 1, 100))
- seq = SeqFormula(sin(x*(y**2 + z)),(z, 1, 100))
- assert seq.expand(trig=True) == SeqFormula(sin(x*y**2)*cos(x*z) + sin(x*z)*cos(x*y**2), (z, 1, 100))
- assert seq.expand() == SeqFormula(sin(x*y**2 + x*z), (z, 1, 100))
- assert seq.expand(trig=False) == SeqFormula(sin(x*y**2 + x*z), (z, 1, 100))
- seq = SeqFormula(exp(x*(y**2 + z)), (z, 1, 100))
- assert seq.expand() == SeqFormula(exp(x*y**2)*exp(x*z), (z, 1, 100))
- assert seq.expand(power_exp=False) == SeqFormula(exp(x*y**2 + x*z), (z, 1, 100))
- assert seq.expand(mul=False, power_exp=False) == SeqFormula(exp(x*(y**2 + z)), (z, 1, 100))
- def test_sequence():
- form = SeqFormula(n**2, (n, 0, 5))
- per = SeqPer((1, 2, 3), (n, 0, 5))
- inter = SeqFormula(n**2)
- assert sequence(n**2, (n, 0, 5)) == form
- assert sequence((1, 2, 3), (n, 0, 5)) == per
- assert sequence(n**2) == inter
- def test_SeqExprOp():
- form = SeqFormula(n**2, (n, 0, 10))
- per = SeqPer((1, 2, 3), (m, 5, 10))
- s = SeqExprOp(form, per)
- assert s.gen == (n**2, (1, 2, 3))
- assert s.interval == Interval(5, 10)
- assert s.start == 5
- assert s.stop == 10
- assert s.length == 6
- assert s.variables == (n, m)
- def test_SeqAdd():
- per = SeqPer((1, 2, 3), (n, 0, oo))
- form = SeqFormula(n**2)
- per_bou = SeqPer((1, 2), (n, 1, 5))
- form_bou = SeqFormula(n**2, (6, 10))
- form_bou2 = SeqFormula(n**2, (1, 5))
- assert SeqAdd() == S.EmptySequence
- assert SeqAdd(S.EmptySequence) == S.EmptySequence
- assert SeqAdd(per) == per
- assert SeqAdd(per, S.EmptySequence) == per
- assert SeqAdd(per_bou, form_bou) == S.EmptySequence
- s = SeqAdd(per_bou, form_bou2, evaluate=False)
- assert s.args == (form_bou2, per_bou)
- assert s[:] == [2, 6, 10, 18, 26]
- assert list(s) == [2, 6, 10, 18, 26]
- assert isinstance(SeqAdd(per, per_bou, evaluate=False), SeqAdd)
- s1 = SeqAdd(per, per_bou)
- assert isinstance(s1, SeqPer)
- assert s1 == SeqPer((2, 4, 4, 3, 3, 5), (n, 1, 5))
- s2 = SeqAdd(form, form_bou)
- assert isinstance(s2, SeqFormula)
- assert s2 == SeqFormula(2*n**2, (6, 10))
- assert SeqAdd(form, form_bou, per) == \
- SeqAdd(per, SeqFormula(2*n**2, (6, 10)))
- assert SeqAdd(form, SeqAdd(form_bou, per)) == \
- SeqAdd(per, SeqFormula(2*n**2, (6, 10)))
- assert SeqAdd(per, SeqAdd(form, form_bou), evaluate=False) == \
- SeqAdd(per, SeqFormula(2*n**2, (6, 10)))
- assert SeqAdd(SeqPer((1, 2), (n, 0, oo)), SeqPer((1, 2), (m, 0, oo))) == \
- SeqPer((2, 4), (n, 0, oo))
- def test_SeqMul():
- per = SeqPer((1, 2, 3), (n, 0, oo))
- form = SeqFormula(n**2)
- per_bou = SeqPer((1, 2), (n, 1, 5))
- form_bou = SeqFormula(n**2, (n, 6, 10))
- form_bou2 = SeqFormula(n**2, (1, 5))
- assert SeqMul() == S.EmptySequence
- assert SeqMul(S.EmptySequence) == S.EmptySequence
- assert SeqMul(per) == per
- assert SeqMul(per, S.EmptySequence) == S.EmptySequence
- assert SeqMul(per_bou, form_bou) == S.EmptySequence
- s = SeqMul(per_bou, form_bou2, evaluate=False)
- assert s.args == (form_bou2, per_bou)
- assert s[:] == [1, 8, 9, 32, 25]
- assert list(s) == [1, 8, 9, 32, 25]
- assert isinstance(SeqMul(per, per_bou, evaluate=False), SeqMul)
- s1 = SeqMul(per, per_bou)
- assert isinstance(s1, SeqPer)
- assert s1 == SeqPer((1, 4, 3, 2, 2, 6), (n, 1, 5))
- s2 = SeqMul(form, form_bou)
- assert isinstance(s2, SeqFormula)
- assert s2 == SeqFormula(n**4, (6, 10))
- assert SeqMul(form, form_bou, per) == \
- SeqMul(per, SeqFormula(n**4, (6, 10)))
- assert SeqMul(form, SeqMul(form_bou, per)) == \
- SeqMul(per, SeqFormula(n**4, (6, 10)))
- assert SeqMul(per, SeqMul(form, form_bou2,
- evaluate=False), evaluate=False) == \
- SeqMul(form, per, form_bou2, evaluate=False)
- assert SeqMul(SeqPer((1, 2), (n, 0, oo)), SeqPer((1, 2), (n, 0, oo))) == \
- SeqPer((1, 4), (n, 0, oo))
- def test_add():
- per = SeqPer((1, 2), (n, 0, oo))
- form = SeqFormula(n**2)
- assert per + (SeqPer((2, 3))) == SeqPer((3, 5), (n, 0, oo))
- assert form + SeqFormula(n**3) == SeqFormula(n**2 + n**3)
- assert per + form == SeqAdd(per, form)
- raises(TypeError, lambda: per + n)
- raises(TypeError, lambda: n + per)
- def test_sub():
- per = SeqPer((1, 2), (n, 0, oo))
- form = SeqFormula(n**2)
- assert per - (SeqPer((2, 3))) == SeqPer((-1, -1), (n, 0, oo))
- assert form - (SeqFormula(n**3)) == SeqFormula(n**2 - n**3)
- assert per - form == SeqAdd(per, -form)
- raises(TypeError, lambda: per - n)
- raises(TypeError, lambda: n - per)
- def test_mul__coeff_mul():
- assert SeqPer((1, 2), (n, 0, oo)).coeff_mul(2) == SeqPer((2, 4), (n, 0, oo))
- assert SeqFormula(n**2).coeff_mul(2) == SeqFormula(2*n**2)
- assert S.EmptySequence.coeff_mul(100) == S.EmptySequence
- assert SeqPer((1, 2), (n, 0, oo)) * (SeqPer((2, 3))) == \
- SeqPer((2, 6), (n, 0, oo))
- assert SeqFormula(n**2) * SeqFormula(n**3) == SeqFormula(n**5)
- assert S.EmptySequence * SeqFormula(n**2) == S.EmptySequence
- assert SeqFormula(n**2) * S.EmptySequence == S.EmptySequence
- raises(TypeError, lambda: sequence(n**2) * n)
- raises(TypeError, lambda: n * sequence(n**2))
- def test_neg():
- assert -SeqPer((1, -2), (n, 0, oo)) == SeqPer((-1, 2), (n, 0, oo))
- assert -SeqFormula(n**2) == SeqFormula(-n**2)
- def test_operations():
- per = SeqPer((1, 2), (n, 0, oo))
- per2 = SeqPer((2, 4), (n, 0, oo))
- form = SeqFormula(n**2)
- form2 = SeqFormula(n**3)
- assert per + form + form2 == SeqAdd(per, form, form2)
- assert per + form - form2 == SeqAdd(per, form, -form2)
- assert per + form - S.EmptySequence == SeqAdd(per, form)
- assert per + per2 + form == SeqAdd(SeqPer((3, 6), (n, 0, oo)), form)
- assert S.EmptySequence - per == -per
- assert form + form == SeqFormula(2*n**2)
- assert per * form * form2 == SeqMul(per, form, form2)
- assert form * form == SeqFormula(n**4)
- assert form * -form == SeqFormula(-n**4)
- assert form * (per + form2) == SeqMul(form, SeqAdd(per, form2))
- assert form * (per + per) == SeqMul(form, per2)
- assert form.coeff_mul(m) == SeqFormula(m*n**2, (n, 0, oo))
- assert per.coeff_mul(m) == SeqPer((m, 2*m), (n, 0, oo))
- def test_Idx_limits():
- i = symbols('i', cls=Idx)
- r = Indexed('r', i)
- assert SeqFormula(r, (i, 0, 5))[:] == [r.subs(i, j) for j in range(6)]
- assert SeqPer((1, 2), (i, 0, 5))[:] == [1, 2, 1, 2, 1, 2]
- @slow
- def test_find_linear_recurrence():
- assert sequence((0, 1, 1, 2, 3, 5, 8, 13, 21, 34, 55), \
- (n, 0, 10)).find_linear_recurrence(11) == [1, 1]
- assert sequence((1, 2, 4, 7, 28, 128, 582, 2745, 13021, 61699, 292521, \
- 1387138), (n, 0, 11)).find_linear_recurrence(12) == [5, -2, 6, -11]
- assert sequence(x*n**3+y*n, (n, 0, oo)).find_linear_recurrence(10) \
- == [4, -6, 4, -1]
- assert sequence(x**n, (n,0,20)).find_linear_recurrence(21) == [x]
- assert sequence((1,2,3)).find_linear_recurrence(10, 5) == [0, 0, 1]
- assert sequence(((1 + sqrt(5))/2)**n + \
- (-(1 + sqrt(5))/2)**(-n)).find_linear_recurrence(10) == [1, 1]
- assert sequence(x*((1 + sqrt(5))/2)**n + y*(-(1 + sqrt(5))/2)**(-n), \
- (n,0,oo)).find_linear_recurrence(10) == [1, 1]
- assert sequence((1,2,3,4,6),(n, 0, 4)).find_linear_recurrence(5) == []
- assert sequence((2,3,4,5,6,79),(n, 0, 5)).find_linear_recurrence(6,gfvar=x) \
- == ([], None)
- assert sequence((2,3,4,5,8,30),(n, 0, 5)).find_linear_recurrence(6,gfvar=x) \
- == ([Rational(19, 2), -20, Rational(27, 2)], (-31*x**2 + 32*x - 4)/(27*x**3 - 40*x**2 + 19*x -2))
- assert sequence(fibonacci(n)).find_linear_recurrence(30,gfvar=x) \
- == ([1, 1], -x/(x**2 + x - 1))
- assert sequence(tribonacci(n)).find_linear_recurrence(30,gfvar=x) \
- == ([1, 1, 1], -x/(x**3 + x**2 + x - 1))
- def test_RecursiveSeq():
- y = Function('y')
- n = Symbol('n')
- fib = RecursiveSeq(y(n - 1) + y(n - 2), y(n), n, [0, 1])
- assert fib.coeff(3) == 2
|